Portrayal of animal communication in wildlife documentary - Andersson, Yrsa (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
Many people turn to documentaries for knowledge about animals, but do documentaries give us a truthful portrayal of animals and their behavior? This study looks at how the communication behavior of the portrayed animals is depicted in three episodes of The Life of Mammals. These episodes were observed after which the contents were compared to scientific literature on the same topics. The results show that quite little communication is actually shown in the episodes about plant predators and meat eaters and relatively much of it is shown in the episode named Social Climbers, involving primates. The matching literature suggests that based on the narrative and the accompanying footage, the viewer is getting a realistic picture, with the exception of a few questionable cases.